Monitoring microbial communities using light sheet fluorescence microscopy - Parthasarathy, Raghuveer (PeerJ Preprints, 2017)
Microbes often live in dense, dynamic, multi-species communities whose architecture and function are intimately intertwined. Imaging these complex, three-dimensional ensembles presents considerable technical challenges, however. In this review, I describe light sheet fluorescence microscopy, a technique that enables rapid acquisition of three-dimensional images over large fields of view and over long durations, and I highlight recent applications of this method to microbial systems that include artificial closed ecosystems, bacterial biofilms, and gut microbiota. I comment also on the history of light sheet imaging and the many variants of the method. Light sheet techniques have tremendous potential for illuminating the workings of microbial communities, a potential that is just beginning to be realized.
Keywords: light sheet fluorescence microscopy; microbial communities; microscopy; microbiota